Potassium channel clustering: mechanisms shaping axonal excitability - Escobedo, Gabriel; Rasband, Matthew N. (Frontiers in Cellular Neuroscience, 2025)
The precise clustering of ion channels at axon initial segments (AIS) and nodes of Ranvier is essential for axonal excitability and rapid action potential propagation. Among the axonal ion channels, voltage-gated potassium channels (Kv) and two-pore domain potassium (K2P) leak channels are key regulators of AIS and nodal excitability. Kv7 and Kv1 channels contribute to action potential threshold and repolarization at the AIS, and membrane repolarization in axons has historically been attributed to Kv channels. However, recent studies suggest that at nodes of Ranvier K2P channels, particularly TRAAK and TREK-1, play a dominant role in action potential repolarization. The interaction of Kv and K2P channels with diverse scaffolding proteins ensures their precise localization at AIS and nodes. Mislocalization or dysfunction of axonal Kv and K2P channels can cause epilepsy and neurodevelopmental disorders. This review explores the diversity of potassium channels and the mechanisms responsible for their clustering at AIS and nodes of Ranvier. Understanding these processes will be essential for therapeutic strategies aimed at treating diseases characterized by abnormal potassium channel expression, clustering, and function in neurons.